2023
DOI: 10.1039/d3ma00779k
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring intra-molecular coupling in BDT-based copolymers to enhance their performance in fullerene-free organic solar cells

Newayemedhin A. Tegegne,
Asfaw Negash,
Desalegn Yilma
et al.

Abstract: By systematically adding acceptors and π-spacers, the structure of a BDT-based copolymer could be tailored to improve their performance in non-fullerene based organic solar cells. A planar geometry increases the complementarity of the copolymer with ITIC, resulting in an efficiency of more than 8%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The dipole moments of the SAMs are expected to facilitate the development of an interfacial dipole at the interface between the ETL and the photoactive layer, possibly aiding charge transfer . Since the dipole moments of the SAMs are due to their electrostatic charge distribution, we further analyzed the electrostatic potential (ESP) of each atom in the SAMs using the Multiwfn 3.7 analyzer . This analysis provided insights into the ESP distribution across the terminal, spacer, and anchor groups of the SAMs as shown in Figure d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dipole moments of the SAMs are expected to facilitate the development of an interfacial dipole at the interface between the ETL and the photoactive layer, possibly aiding charge transfer . Since the dipole moments of the SAMs are due to their electrostatic charge distribution, we further analyzed the electrostatic potential (ESP) of each atom in the SAMs using the Multiwfn 3.7 analyzer . This analysis provided insights into the ESP distribution across the terminal, spacer, and anchor groups of the SAMs as shown in Figure d.…”
Section: Resultsmentioning
confidence: 99%
“…30 Since the dipole moments of the SAMs are due to their electrostatic charge distribution, we further analyzed the electrostatic potential (ESP) of each atom in the SAMs using the Multiwfn 3.7 analyzer. 31 This analysis provided insights into the ESP distribution across the terminal, spacer, and anchor groups of the SAMs as shown in Figure 1d. The results revealed that the silane anchor group exhibits a much more negative ESP of −1.8 eV compared to the thiol group (−0.65 eV).…”
Section: ■ Introductionmentioning
confidence: 99%